2003
DOI: 10.1002/chp.1340230205
|View full text |Cite
|
Sign up to set email alerts
|

Commitment to change statements can predict actual change in practice

Abstract: In three of four indicator conditions, physicians who expressed a commitment to change were significantly more likely to change their actual prescribing for the target medications in the following 6 months. The percentage of physicians who did change their prescribing varied significantly by condition. Further study of the process of translating commitment to change into real practice change is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
133
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(138 citation statements)
references
References 22 publications
4
133
1
Order By: Relevance
“…21,22 These study results indicate that self-reported changes can be a proxy for actual change. 21,22 A second limitation of our study includes the potential for reporting bias of the nonresponders. 24 Nonresponders may be uncomfortable reporting their potential inability to implement changes.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…21,22 These study results indicate that self-reported changes can be a proxy for actual change. 21,22 A second limitation of our study includes the potential for reporting bias of the nonresponders. 24 Nonresponders may be uncomfortable reporting their potential inability to implement changes.…”
Section: Discussionmentioning
confidence: 68%
“…Other investigators have implemented the commitment-to-change strategy to evaluate CME/CE programs. [19][20][21][22][23][24][25][26][27][28][29] Most of these studies included a small number of participants (Nϭ26-84), [19][20][21][23][24][25]27 and only 3 included nonphysician clinicians. 24,25,27 A total of 952 of 971 (98.0%) of the commitments written by clinicians attending our CME/CE program were directly related to learning objectives, and all learning objectives had at least one commitment statement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10] These are simply written statements in which participants commit to making a change in their future behavior or practice. The statement may or may not be signed.…”
Section: Introductionmentioning
confidence: 99%